Pome treatment technology using biological and physical method: a review / Noor Sahira Noor Azizan - Noor Azizan, Noor Sahira (Faculty of Plantation and Agrotechnology, 2018)
Oil palm or Elaeis guineensis is a species of palm usually known as African oil palm. Recently, palm oil from the oil palm has become the world’s most popular vegetable oil due to high quantity of production. Palm oil mills have been declared as one of the main source of environmental pollution as it generates both solid and liquid wastes. The palm oil plantations must implemented various measures to lessen the environmental impact. The solid waste are known as Sludge Palm Oil (SPO) while the liquid waste is Palm Oil Mill Effluent (POME). Other than that, the increasing in the waste production had generated by the increase of palm oil production eventually. Generally, Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) are essential parameters used as indicators of composition and environmental impact of waste water. The high COD value is responsible for distraction of aquatic life. POME can be treated by using algae and selected aquatic plants in biological method. Research has been conducted to Chlamydomonas incerta, Pistia stratiotes, Ipomoea aquatica, Chrysopogon zizanioides and Eichhornia crassipes. The result has showed that the Eichhornia crassipes was able to reduce COD, BOD, N and P up to 50%, 90%, 88% and 64% respectively. Meanwhile for the SPO, it can be treated by physical method which is composting. Therefore, Eichhornia crassipes is the most effective biological method for POME treatment because their percentage in effectiveness in reduce contaminants is higher than other aquatic plants and microalgae. This review discusses the several potential method that are accepted and being observe in related research and also make comparison between biological and physical method of POME treatment.